The Concept of Fai’ (Spoils of War) and the Evolution of its Meanings in the Prophetic Era and the Rashidun Caliphs - Al-Momani, Mohammad Khaled (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: The current study aims to explore the linguistic and terminological aspects of Fay’ and its theoretical and practical evolution during the era of Prophethood and the Rashidun Caliphs. Additionally, the study seeks to examine the practical applications of the concept of Fay’, including new interpretations, developments, and exceptions that emerged during these periods. Methods: The study employed an analytical approach, gathering information through investigation based on the Holy Quran, Prophetic traditions, and historical narratives from the era of Prophethood and the Rashidun Caliphs, marked by jihad and the initiation of Islamic conquests. The collected data were understood, sorted, classified, and analyzed according to their respective time periods and practical applications, leading to the extraction of results. Results: The study found that Fay’ refers to what returns to Muslims hands from non-Muslims through peaceful agreements or forced acquisition of lands, properties, and possessions. The evolution of the concept of Fay’ was shaped by interpretations that varied over time, encompassing meanings such as spoils of war, jizyah (tax on non-Muslims), and khiraj (land tax). It also extended to the combination of jizyah, khiraj, trade tithes (ushr), and sadaqat al-suf (charitable contributions). The Prophet Muhammad (peace be upon him) applied Fay’ in ways that benefited Muslims according to Islamic governance principles. Abu Bakr (may Allah be pleased with him) followed the same approach, while Caliphs Umar ibn al-Khattab and Uthman ibn Affan (may Allah be pleased with them) managed Fay’ by halting further land expansion and channeling its proceeds to the Muslim treasury. Conclusions: The semantic and evolutionary clarification of the concept of Fay’ in relation to its meanings, adapting to changing circumstances of time and place, both theoretically and practically, clarifies its application in light of relevant conditions, developments, and the associated time period.